Assessing the Level of Comparative Advantage for the Boro Rice Production in Bangladesh: A Time Series Analysis - Mohammad Ariful Islam; Md. Abdur Rouf Sarkar; Mohammad Chhiddikur Rahman; Md. Shajedur Rahaman (Journal of Bangladesh Agricultural University, 2021)
This study aims to investigate whether Bangladesh has a comparative advantage in producing rice in the long run for the Boro season. With that view, we estimated “Domestic Resource Cost (DRC)” as an indicator of comparative advantage using the time series data. Data were obtained from the food situation database, published by the Food Planning and Monitoring Unit, Ministry of Food, Peoples' Republic of Bangladesh. The analyses show that Bangladesh has a comparative advantage in modern rice production in the Boro season at import substitution. DRC values for Boro season are less than 1 in all the periods (2010/11 to 2019/20) except 2018/19. The sensitivity analysis shows that all the indicators pertinent to this particular analysis strongly influence DRC values. The government and policymakers should focus on price spread between the wholesale to retail levels, the border price of rice at the farm gate level, and the border prices of rice, urea, TSP, and MoP of farm gate level to achieve a long-run comparative advantage. Research efforts need to be prioritized for developing new varieties, especially for the Boro season with higher yield potential.
Keywords: 330; Boro season rice; DRC; Tradable inputs; Sensitivity; Time series; Bangladesh